2013
DOI: 10.1007/s00216-013-7128-2
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the depth of mass spectrometry-based glycomic coverage by additional dimensions of sulfoglycomics and target analysis of permethylated glycans

Abstract: Hog or porcine gastric mucin resembles the human source in carrying not only blood group antigens but also the rather rare α4-GlcNAc-capped terminal epitope functionally implicated in protection against Helicobacter pylori infection. Being more readily available and reasonably well characterized, it serves as a good reagent for immunobiological studies, as well as a standard for analytical methodology developments. Current approaches in mass spectrometry (MS)-based glycomic mapping remain vastly inadequate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…The former set of ions resulting from concerted cleavages at the GalNAcitol (see schematic drawing in Fig. 2) has been previously observed under negative ion mode MALDI-MS/MS of sulfated O-glycans 21,23 , which firmly establishes the 6-arm substituents. It is clear that an isomeric structure II carrying instead a non-fucosylated sulfated LacNAc on the 6-arm also existed, as indicated by the B ions at m/z 528, its analogous satellite ions at m/z 588, 616, 632, 676, 745, and 759, and the Z 1 and Y 1 ions at m/z 789 and 807.…”
Section: Resultsmentioning
confidence: 72%
“…The former set of ions resulting from concerted cleavages at the GalNAcitol (see schematic drawing in Fig. 2) has been previously observed under negative ion mode MALDI-MS/MS of sulfated O-glycans 21,23 , which firmly establishes the 6-arm substituents. It is clear that an isomeric structure II carrying instead a non-fucosylated sulfated LacNAc on the 6-arm also existed, as indicated by the B ions at m/z 528, its analogous satellite ions at m/z 588, 616, 632, 676, 745, and 759, and the Z 1 and Y 1 ions at m/z 789 and 807.…”
Section: Resultsmentioning
confidence: 72%
“…In separate experiments, 4M-f1 was shown to be bound by a monoclonal anti-H type 2 but not anti-H type 1 (data not shown). Taking into account the F77 antigen activity of the branched blood group B glycolipid BIII and the lack of detection of type 1 backbones in a detailed study of the O -glycans of PSM (28), the proposed oligosaccharide sequence of 4M-f1 is a blood group H on a branched backbone of the I-antigen type (29), originating from the C6 position of the core GalNAcol as depicted in Scheme 1. Thus, we propose that the parent O -glycan alditol before periodate oxidation was at least the octasaccharide shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…The microarray data in the small-scale experiments, using as little as ϳ1 mg of O-glycan alditols, showed that ligand-containing fractions can be readily detected by this approach with associated MALDI-MS monitoring. The ligand-positive hexasaccharide with the blood group H type 1 sequence (rather than H type 2) has not been described in PSM to our knowledge (37). With optimization of the O-glycan derivatization step there is scope for a substantial increase of yields.…”
Section: Discussionmentioning
confidence: 99%